Integrating replicated network with looping method for multistage interconnection network reliability - Md Yunus, Nur Arzilawati (2022)
Multistage Interconnection Network provides communication in parallel and high-performance computer systems related to memory modules, processors, and other devices. These networks are considered to offer a reasonable cost of implementation with efficient and fast communication. The interconnection topology, number of stages, and network configuration differentiate the reliability of each network. Reliability measurement for each network depends on the system performance component's reliability to deliver the information from source to destination pairs. This thesis analyses the reliability performance in the shuffle exchange network environment. Shuffle Exchange Network and Augmented Shuffle Exchange Network are the types of MIN. In this network, the main problem arises when the switching element fails to route in the stages. Therefore, there is a concern to provide fault tolerance network to create a redundant path with an additional link between the source and destination communication. Enhanced Augmented Shuffle Exchange Network implementing the final looping method at the last stage to helps enhance the fault tolerance in the network, leading to higher reliability performance up to 16.65% and 1.11% as compared to SEN and ASEN. The final looping and double looping features help to minimize the failure at any links by providing an additional auxiliary link. Then, the alternate paths can be utilized in case of a fault in a path. Due to link and switch failure, all the data from the source are not possible to be sent to the same destination simultaneously by using a single path network. Therefore it is essential to design a network that provides multipath data transmission. In this thesis we proposed, the integration of replicated network to Shuffle Exchange Network, Augmented Shuffle Exchange Network, and Enhanced Augmented Shuffle Exchange Network topology. We replicate the network into two layers for each network. The increasing number of layers will improve the reliability performance result within the network up to 13.65% and 1.62% as compared to SEN and ASEN. The replicated network features provide more availability of redundant paths in the network. A common problem in network design is creating a reliable and cost-effective network. Network topologies can connect links to different nodes, communicating with each other to transfer data. In addition, this thesis also integrates the hybrid network combination of Shuffle Exchange Network with Additional Stages and Benes network known as Shuffle Exchange Benes Interconnection Network. The implementation of Benes topologies in Shuffle Exchange Network makes a resultant topology that has advantages of Benes topology instead of having only Shuffle Exchange Network topology. This hybrid network consists of fewer switching since we reduce one stage from the Benes topology and combine with the Shuffle Exchange Network with Additional Stages to reduce the 20% of hardware cost.